Analysis of pharmaceutical market of dietary supplements with green tea leaves extract - O. Yu. Maslov; S. V. Kolisnyk; M. A. Komisarenko; S. M. Poluian; M. Yu. Holik; T. O. Tomarovska (Zaporozhye State Medical University, 2022)
The aim of work is to study the assortment of dietary supplements with green tea leaves extract on the modern pharmaceutical market to further search for ways to improve and optimize pharmaceutical supply. Materials and methods. The assortment of dietary supplements with green tea leaves extract was studied basing on the search of dietary supplements in pharmacies of Ukraine in the internet resources. For study of assortment of dietary supplements, the following methods were used: marketing, statistical, logic and graphic. Results. The assortment of dietary supplements with green tea leaves extract has been analyzed. The results showed that the leaders in the number of manufacturers in the analyzed group of dietary supplements are the United States, Ukraine, and Poland, their part is 61 %, 16 % and 8 %, respectively. In terms of assortment, the United States ranks first - 66 %. Dietary supplements are presented in 6 dosage forms, most of them are capsules (60 %). It was determined that monopreparations predominate in the pharmaceutical market and account for 77 %. The price segmentation of the market of dietary supplements with green tea leaves extract has been provided, the results showed that most of these are dietary supplements in the price range of 200-500 UAH. The study of the company structure made it possible to identify leaders among foreign companies; the top three companies included Now Foods (27 %), Swanson (20 %), Puritan's Pride (14 %). Conclusions. There are 42 dietary supplements with green tea leaves extract at the beginning of 2022 in Ukraine. On the temporary pharmaceutical market of Ukraine 84 % of dietary supplements with green tea extract are presented by foreign manufacturers, mainly by monopreparations, in the form of capsules and in the price range from 200 to 500 UAH.